Impact of organizational factors on delays in BIM-based coordination from a decision-making view: a case study - Jang, Sejun; Lee, Ghang (Journal of Civil Engineering and Management, 2018)
This study analyzed the impact of organizational factors on delays in building information modeling (BIM)- based coordination for mechanical, electrical, and plumbing (MEP) systems from the decision-making perspective. Recently BIM-based coordination has been regarded as a critical phase in project delivery but suffers from delays during the coordination process. This study investigated three complexity factors that often contribute to coordination delays: the number of participants – the total number of participants involved in a decision-making process for resolving a coordination issue; the level of the decision makers – the highest decision-maker involved in a problem-resolution process; and the heterogeneity of participants –the number of trades related to an issue. Using 95 major coordination issues derived from 11,808 clashes in a case study, the correlations between the coordination time and the complexity factors were analyzed. The coordination time linearly increased as each factor increased. The number of participants had the highest correlation with the coordination time, followed by the level of decision makers and the heterogeneity of participants. The findings stress the significance of integration between BIM and lean approaches, such as Obeya (big room) and Shojinka (flexible manpower line), during BIM-based coordination to expedite decision-making processes and eventually to reduce the coordination time.